Effect of Competence on Career Development and Implication for Organizational Commitment - Shinta Dewi Suprayitno; Survival; Dharmayanti Pri Handini (Optima Science, 2023)
Every employee might have different competence. The incompatibility between this competence and the job responsibility could influence career development and loyalty. Any public institution must deal with this issue to improve human resource quality. The purpose of this study is to examine the effect of competence on organizational commitment and to find out the implication of this effect for organizational commitment of BLU Education Personnel of Non-Civil Servants at the Health Polytechnic of the Health Ministry in Malang. Population of this study includes 53 individuals. Probablity sampling is used as sampling method with proportional simple random sampling as sampling technique. The size of sample is determined with Slovin Formula which produces 35 respondents. Data collection technique involves observation, interview, and questionnaire. Data analysis employs Smart Partial Least Square (PLS) software. Several results are obtained from this study. Competence has positive and significant effect on career development. Competence also has positive and significant effect on organizational commitment. Career development has positive and significant effect on organizational commitment. Competence has positive and significant effect on organizational commitment with the mediation of career development.